Jim Cramer's get rich carefully - Cramer, Jim (Blue Rider Press, a member of Penguin Group (USA), 2013)
" Tired of phony promises about getting rich quickly, promises that lead to reckless decisions (the stepping stones to the poor house)? How about trying something different? How about going for lasting wealth-and doing it the cautious way? In Get Rich Carefully, Jim Cramer uses his thirty-five years of experience as a Wall Street veteran and host of CNBC's Mad Money to create a guide to high-yield, low-risk investing. In our recovering economy, this is the plan you need to make big money without taking big risks. Drawing on his unparalleled knowledge of the stock market and on the mistakes and successes he's made on the way to his own fortune, Cramer explains-in plain English-why you can get rich in a prudent, methodical way, as long as you start now. In his own inimitable style, Cramer lays it on the line, no waffling, no on-the-one-hand-or-the-other hedging, just the straight stuff you need to accumulate wealth. This is a book of wisdom as well as specifics. Cramer names names, highlights individual and sector plays, and identifies the best long-term investing themes-and shows you how to develop the disciplines you need to exploit them. The personal finance book of the year, Get Rich Carefully is the invaluable guide to turning your savings into real, lasting wealth in a practical, and yes-because this is, after all, a book by Jim Cramer-highly readable and entertaining way"--